Inhibitors of JmjC-containing histone demethylases - Wright, M; Kawamura, A; Brennan, PE (Springer, 2020)
Histone demethylases (KDMs) catalyse the removal of N-methyl marks on histones and play important roles in epigenetic regulation. Abnormal histone methylation and dysregulation of KDMs have been linked to multiple diseases, and KDMs are emerging as promising therapeutic targets. This chapter provides an overview of JmjC-domain-containing KDMs (JmjC-KDMs), with a particular focus on recent advances in JmjC-KDM inhibitor development from a structural perspective.